Analysis of Cost Budgeting as a Management Control Tool at Nike Inc. - Pratiwi, Tio; Dewi, Ratna (Maksi, 2024)
The cost budgeting policy emphasizes the preparation of budgets and revenues. A thorough analysis is the first step to ensure that the budget developed accurately reflects the actual situation. This study was conducted at Nike Inc. to determine whether cost control could assist management. The author discovered that the preparation of cost budgets presents a challenge due to the differences (variations) between the budget and actual results, which are reflected in favorable or unfavorable variances. The findings suggest that the role of cost budgeting in Nike Inc.'s management control functions has not yet reached its full potential, as negative deviations are still present. This research explores the role of cost budget analysis as a management control tool at Nike Inc. Effective budgeting plays a crucial role in planning, coordinating, and controlling company resources to achieve organizational objectives. By analyzing the implementation of budgeting and cost management practices at Nike Inc., this article highlights how budgeting serves as a framework for decision-making and performance evaluation. The study uses both qualitative and quantitative approaches, utilizing financial data, reports, and management strategies implemented by Nike Inc. The findings emphasize that cost budget analysis is essential in optimizing resource allocation, minimizing deviations, and aligning operational activities with company objectives. The study underscores the importance of a robust budget control mechanism to maintain financial discipline and enhance overall organizational efficiency.